Nas veredas do sertão colonial: o processo de conquista e a formação de elites locais no sertão de Piranhas e Piancó (Capitania da Parahyba do Norte, c.1690-c.1772) - Formiga, Mayara Millena Moreira (2013)
This study has as main objective of analyze the conquest and the occupation of hinterland of the Captaincy of Paraiba North as well as the formation of the first local elites that were forming in the region between the years 1690-1772. During these years the hinterland of the North Capitanias of the State of Brazil went through a process of internalization of their territories, especially after the expulsion of the Holandeses in 1654. Like this, we undertook an investigation about the process that precedes the establishment of the settlers in the hinterland of Piranhas and Piancó: the war against indigenous peoples and the distribution of land allotments. This tense process of disputes could not have been successful without the participation of conquerors who, at the expense of their strengths and resources, and by strength of sword and of faith, dilated else the Portuguese dominions in America. Finally we seek to understand how the first conquerors of the region analyzed here, especially the family group of Oliveira Ledo, became the first and principal nucleus of the local elite, through access to real mercês granted by the monarch through the services provided under the achievement.